STRUCTURAL AREAS IN EAST EUROPEAN ALPINE FOLDED BELT: CONTRASTING PHYSICAL PROPERTIES OF VOLCANIC PRODUCTS - Tolstoy, M.; Shabatura, O.; Kostenko, N.; Hasanov, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Multiparameter contrasting of volcanites physical properties in the various zones of the Alpine orogen showed the greatest similarity between the objects related to a common volcanic province. This defines a territorial principle to be leading for petrophysical analysis. Substance-sensitive parameters, such as mineral density, thermal conductivity, and others become decisive for objects homogeneity. However, their significance gradually decreases as new high-order links appear. While the affect of the territorial proximity decreases, the importance of structural petrophysical parameters, such as overall and effective porosity, elasticity, velocity etc. increases. Density and porosity are crucial for strong homogeneity between geological objects, while inductive magnetic parameters and elastic velocity determine weak territorial proximity. The correlation between vulcanite phases, chemistry, and their physical properties varies widely in different geological objects. For andesitebasalts and dacite-rhyolite series, chemical constancy and physical properties were established to be primarily determined by the geological environment of their origin, regardless of the age or territorial proximity. Differences in structural-tectonic position, mode of crystallization recorded by structural-sensitive physical properties have nominally higher and divergent values, and, therefore, are more informative for geological and territorial section fragmentation. For instance, structure-sensitive petrophysical properties are most appropriate to assess a depth of magma chambers. As the depth increases, elasticity and uniform stress moduli gradually decrease. At the same time there is traced an intermittent decrease in Poisson's ratio, longitudinal and transverse wave velocity, as well as Vp/Vs shear ratio is recorded. Research into structural-sensitive properties reveals similarity between basalts and andesite-basalts located in Hungary, Armenia, Western Carpathians, and the Caucasian regions. Andesite-basalts, basalts, and dacites of the central trans-Carpathians, Kazbek and Elbrus are similar in VP/Vs values. There were singled out a number of petrophysical regularities for volcanites in different zones of the Alpine orogen. The mentioned above are as following: lateral petrophysical zonality (Carpathian segment); a strong differentiation of magnetic characteristics of the Caucasus and Armenia; a stable inverse dependence of elastic and thermal properties on the value of total porosity (all objects under research).
Keywords: physical properties; volcanites; petrophysical analysis